2020
DOI: 10.1371/journal.pone.0228887
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in POT1 and risk of thyroid subsequent malignant neoplasm: A report from the Childhood Cancer Survivor Study

Abstract: BackgroundTelomere length is associated with risk for thyroid subsequent malignant neoplasm in survivors of childhood cancer. Here, we investigated associations between thyroid subsequent malignant neoplasm and inherited variation in telomere maintenance genes. MethodsWe used RegulomeDB to annotate the functional impact of variants mapping to 14 telomere maintenance genes among 5,066 five-or-more year survivors who participate in the Childhood Cancer Survivor Study (CCSS) and who are longitudinally followed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Although a number of studies show telomere shortening to be associated with cancers of the thyroid [6,23,24], mutations in POT1 are predicted to cause telomere lengthening and increase susceptibility to various cancers [25]. A study on participants of the Childhood Cancer Survivor Study identified an association between a low-frequency intronic regulatory variant in POT1 and the risk for thyroid subsequent malignant neoplasm in the survivors and provided evidence that the variant may be related to longer TL [26]. Thus, the cancer-telomere length paradox is a known phenomenon and requires further research before a consensus can be reached.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies show telomere shortening to be associated with cancers of the thyroid [6,23,24], mutations in POT1 are predicted to cause telomere lengthening and increase susceptibility to various cancers [25]. A study on participants of the Childhood Cancer Survivor Study identified an association between a low-frequency intronic regulatory variant in POT1 and the risk for thyroid subsequent malignant neoplasm in the survivors and provided evidence that the variant may be related to longer TL [26]. Thus, the cancer-telomere length paradox is a known phenomenon and requires further research before a consensus can be reached.…”
Section: Discussionmentioning
confidence: 99%
“…Germline POT1 mutations have been initially described as increasing the risk of melanoma, but later studies indicate a broader cancer spectrum associated with these mutations. Notably, POT1 mutations have recently been associated with familial non-medullary thyroid cancer [ 40 , 41 , 42 ]. A duplicity of thyroid cancer with melanoma has been identified in a patient with a newly characterized splicing POT1 mutation (thyroid cancer was present in the patient’s untested mother’s mother).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the POT1 variant rs35439397 has been associated with poor survival in breast cancer [ 131 ]. In survivors of childhood cancer, the presence of the POT1 rs58722976 variant has been linked with an increased risk of developing a subsequent thyroid cancer [ 132 ]. In CLL, a four-gene panel that includes POT1 , XPO1 , MYC88 and BIRC3 can predict reduced survival in CLL and monoclonal B-cell lymphocytosis [ 83 ].…”
Section: Clinical Implications Of Pot1 Alterations In Cancermentioning
confidence: 99%